Method for preparing composite building material

By mixed the construction waste and plastic waste combined and solidified under anaerobic conditions, the problem of not using cement production materials in existing technologies in existing technology has been solved, and it has achieved efficient use of waste, reducing CO2 emissions, and promoting carbon carbon. Neutral effect.

CN119371138APending Publication Date: 2025-01-28THE HONG KONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411001259.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-24
Filing Date
2024-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art has difficulty in efficiently producing sustainable building materials that do not use cement, especially in the efficient recycling and reuse of construction and plastic waste.

Method used

By mixing the construction waste and plastic waste, solidify under anaerobic conditions at a temperature close to or higher than the melting point of plastic waste to form composite building materials. This method can not only effectively use building waste and plastic waste, but also avoid the use of cement and reduce CO2 emissions.

Benefits of technology

Achieved converting building waste and plastic waste into economic value -free materials, improved the strength and application range of materials, simplified the process of waste classification and solidification, reduced the dependence of carbon -dense setting materials, promoted to promote Carbon neutral.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371138A_ABST
    Figure CN119371138A_ABST
Patent Text Reader

Abstract

A method for preparing a composite building material, the method comprising: combining plastic waste and building waste, such as building debris, macadam, stone, concrete rubble, earth, or a mixture thereof, to form a waste mixture; and solidifying the waste mixture under anaerobic conditions, thereby melting or softening at least a portion of the plastic waste and forming the composite building material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 515,346, filed on July 25, 2023, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present disclosure relates to a method for producing cement-free materials. More specifically, the present disclosure provides a production method using construction waste and plastic waste without adding cement. Background Art

[0004] The growing global population and frequent human activities are increasing the emission of greenhouse gases, especially carbon dioxide (CO 2 )) emissions, which accelerates global warming and causes climate change. According to the Intergovernmental Panel on Climate Change (IPCC, 2019), when the global average temperature rises by 1.5℃ above the pre-industrial level between 1850 and 1900, ecosystems, biodiversity and ice sheets will experience irreversible losses, endangering food production and human life. In order to avoid global temperature rise, it is necessary to reduce global CO2 emissions by about 2050. 2 Net emissions are reduced to zero. As a result, most countries in the world have committed to responding to the climate action framework of the Paris Agreement and are fully committed to sustainable development and carbon neutrality.

[0005] The construction industry is the world’s largest CO 2 Concrete is one of the main sources of CO emissions. In general, concrete is a building material commonly used in various scenarios including road pavements, walls, buildings, etc. It consists of cement and natural aggregates (e.g., sand, rocks, stones, etc.), which can be defined as binders and fillers, respectively. However, the production of cement is energy intensive, accounting for 2.5% of global CO emissions. 2 Emissions are about 10% (Monteiro et al., 2017). Each ton of cement produced generates nearly one ton of CO 2 When constructing a building, about 60% of CO 2Emissions can be attributed to the production of materials (UKGBC, 2015). In addition, during construction projects (such as building demolition, renovation, ground leveling, road paving, etc.), construction materials can be processed and become waste. Since most construction waste is inorganic and inert, it is generally dumped in landfills. This may contaminate soil and groundwater and even cause land degradation. According to statistics from the US Environmental Protection Agency, the European Union and Chinese research institutions, construction waste accounts for 15% to 70% of the total municipal solid waste (MSW) in these countries (QIRI, 2018; USEPA, 2020; Eurostat, 2022). Therefore, there is an increasing call for the development of sustainable building materials as alternatives to conventional options to minimize CO 2 emissions and waste generation.

[0006] In addition to construction waste, plastic waste is another major MSW that countries need to deal with. At present, the global annual plastic production has reached nearly 390 million tons, an increase of nearly 260 times compared with 1950 (Statista, 2023). The increase in plastic production is also accompanied by serious waste generation. At present, the recycling rate of plastic waste is still relatively low, and most plastic waste is solved by landfill. For example, only about 9% of plastic waste in the United States is recycled, while nearly 76% of plastic waste is disposed of in landfills (USEPA, 2020). Although incineration can efficiently treat non-biodegradable plastic waste, a large amount of CO is emitted in the process. 2 . The CO emitted 2 This is equivalent to three times the mass of incinerated plastic (Vollmer, 2020). In view of this, there is an urgent need to address the issue of construction waste at the same time, invent sustainable technologies to recycle and reuse both types of waste and promote carbon neutrality. The ideal situation would be to be able to incorporate recycled waste into building materials to minimize CO2 emissions from the construction industry. 2 Emissions.

[0007] To make concrete sustainable, most research is directed towards using construction and plastic waste to replace part of the natural aggregates (i.e., sand, rocks, stones, etc.) in concrete. In the past decade, more than a hundred studies have examined the properties of concrete composed of construction and plastic waste as aggregates. Although waste can be reused, this method requires the addition of additional cement to bind the aggregates, which results in CO emissions. 2On the other hand, the feasibility of using plastic waste to replace some binders in construction materials has also been explored. Among them, mixing polyethylene (PE) in asphalt has been tried for road pavement construction. When the asphalt is heated during pavement construction, PE also melts and bonds natural aggregates. Obviously, such methods are only applicable to specific types of plastic waste (i.e., PE) and asphalt-based materials, and carbon-intensive asphalt is still the main binder. These factors limit the efficiency of plastic waste recycling and reuse and restrict the application of the produced materials. Recently, people have tried to heat plastic waste (e.g., PE and polypropylene (PP)) to replace cement for bonding natural aggregates (Dalhat and Wahhab, 2016). The working principle is to first increase the heating temperature to achieve melting, and then compact the molten mixture to form a specimen. However, during heating, plastic waste may oxidize because the mixture contains impurities including aggregates themselves. This releases toxic fumes and causes the plastic to degrade or burn, thereby failing to achieve the intended goal of becoming a binder. Most plastic waste cannot be guaranteed to become a binder simply by heating. Studies have found that adding more plastic waste to fired bricks further reduces the strength of the bricks (Akinyele et al., 2020). In addition, it is necessary but relatively impractical to precisely control the temperature of plastic waste near its melting point, because the boundary temperature (e.g., heating elements, molds, etc.) can affect the melting of plastics and even cause them to burn (Sun et al., 2022). More importantly, construction waste is not recycled and reused in this type of technology.

[0008] In fact, there is currently no method for efficiently producing sustainable materials using only construction waste and plastic waste without cement. Therefore, there is a need for improved methods for producing composite building materials from construction waste and plastic waste to address or overcome at least some of the above-mentioned shortcomings. In addition, other desirable features and characteristics will become apparent from the following detailed description and the appended claims, taken in conjunction with the accompanying drawings and the background of the present disclosure. Summary of the invention

[0009] This article describes a method for producing sustainable materials. This production only requires construction waste and plastic waste, without the use of cement. Construction waste and plastic waste used as filler and adhesive respectively are uniformly mixed. The waste mixture is first molded and solidified at a temperature close to and above the melting point of the plastic waste. The environment of the solidified mixture can be supplied with an inert gas (e.g., nitrogen, carbon dioxide, etc.) or under vacuum, thereby avoiding oxidation (e.g., burning) of the waste and the release of toxic gases. Plastic waste can contain single or multiple types of plastics, simplifying the requirements of waste classification and purification. After solidification, plastic waste bonds and reinforces construction waste to form new sustainable materials.

[0010] This method not only converts both construction waste and plastic waste into cement-free materials that are suitable for a variety of applications and have economic value, but also reduces CO by upcycling waste and minimizing the use of conventional carbon-intensive construction materials (e.g., cement). 2 emissions and achieve carbon neutrality.

[0011] In a first aspect, the present disclosure provides a method for preparing a composite building material, the method comprising: combining plastic waste and construction waste to form a waste mixture; and solidifying the waste mixture under anaerobic conditions to melt or soften at least a portion of the plastic waste and form a composite building material.

[0012] In certain embodiments, the construction waste includes concrete, asphalt, asphalt, rubble, rock, aggregate, building debris, crushed stone, stone, concrete rubble, earth, broken glass, bricks, tiles, ceramics, drywall, or mixtures thereof.

[0013] In certain embodiments, the plastic waste comprises polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polystyrene, acrylonitrile butadiene styrene, polycarbonate, nylon, polymethyl methacrylate, polylactic acid (polylactide), polyether sulfone, polyoxymethylene, polyether ether ketone, polyetherimide, polyphenylene ether, polyphenylene sulfide, polyvinylidene fluoride, polytetrafluoroethylene, or a mixture thereof.

[0014] In certain embodiments, the plastic waste comprises polyethylene, polypropylene, or a mixture thereof.

[0015] In certain embodiments, the composite building material includes at least 5% plastic waste, relative to the total weight of plastic waste and construction waste.

[0016] In certain embodiments, the composite building material includes at least 10% plastic waste, relative to the total weight of plastic waste and construction waste.

[0017] In certain embodiments, the step of combining plastic waste and construction waste further comprises combining water to form a waste mixture having a water content of 5 to 20% by weight; and molding the waste mixture prior to solidifying the waste mixture.

[0018] In certain embodiments, solidifying the waste mixture is carried out at a temperature of ±20°C of the melting point of the plastic waste.

[0019] In certain embodiments, solidifying the waste mixture is carried out at a temperature of ±5°C of the melting point of the plastic waste.

[0020] In certain embodiments, the method further comprises the step of determining the melting point of the plastic waste.

[0021] In certain embodiments, oxygen-free conditions include vacuum or an inert atmosphere including nitrogen, carbon dioxide, helium, argon, or mixtures thereof.

[0022] In certain embodiments, the composite building material has an unconfined compressive strength of at least 2.4 MPa as measured according to ASTM D2166M-16.

[0023] In certain embodiments, the construction waste comprises building debris, crushed stone, stone, concrete rubble, earth or a mixture thereof; the plastic waste comprises polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polystyrene or a mixture thereof; the composite building material comprises at least 5 to 40% plastic waste relative to the total weight of the plastic waste and the construction waste; the solidification of the waste mixture is carried out at a temperature of ±20°C of the melting point of the plastic waste; and the anaerobic conditions comprise a vacuum or an inert atmosphere, the inert atmosphere comprising nitrogen, carbon dioxide, helium, argon or a mixture thereof.

[0024] In certain embodiments, the construction waste comprises building debris, crushed stone, stone, concrete rubble, earth or a mixture thereof; the plastic waste comprises polyethylene, polypropylene or a mixture thereof; the composite building material comprises at least 10% to 40% plastic waste relative to the total weight of the plastic waste and the construction waste; the solidification of the waste mixture is carried out at a temperature of ±5°C of the melting point of the plastic waste; and the anaerobic conditions comprise a vacuum or an inert atmosphere, the inert atmosphere comprising nitrogen, carbon dioxide, helium, argon or a mixture thereof.

[0025] In certain embodiments, the composite building material has an unconfined compressive strength of 2.4 MPa to 7 MPa as measured according to ASTM D2166M-16.

[0026] In certain embodiments, the method further comprises the step of determining the melting point of the plastic waste.

[0027] In certain embodiments, the method further comprises applying a surface treatment to at least one surface of the composite building material, wherein the surface treatment comprises a radiative cooling coating, a radiative cooling paint, or a mixture thereof.

[0028] In certain embodiments, the radiative cooling coating comprises silicone and a metal oxide selected from the group consisting of magnesium oxide, aluminum oxide, titanium oxide, and silicon oxide.

[0029] In certain embodiments, the radiative cooling coating includes titanium dioxide, barium sulfate, and polyvinylidene fluoride-hexafluoropropylene copolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and other objects and features of the present disclosure will become apparent from the following description of the present disclosure in conjunction with the accompanying drawings.

[0031] Figure 1 Represents the unconfined compressive strength of construction waste alone after curing at four different temperatures. Note: Three replicates were conducted at each temperature.

[0032] Figure 2 It represents the unconfined compressive strength of construction waste mixed with different amounts of plastic waste (i.e., PE) after curing at 150°C in air. Note: The strength is expressed as mean ± standard error, n=3.

[0033] Figure 3 It represents the unconfined compressive strength of construction waste mixed with different amounts of plastic waste (i.e., PP) after curing in air at different temperatures. Note: The strength is expressed as mean ± standard error, n = 3.

[0034] Figure 4 The unconfined compressive strength of construction waste containing 5% PP after curing at 185°C in different types of gases is plotted. Note: The strength is expressed as mean ± standard error, n = 3.

[0035] Figure 5 The unconfined compressive strength of construction waste mixed with different amounts of PP after curing at 185°C in vacuum is presented. Note: The strength is expressed as mean ± standard error, n = 3. DETAILED DESCRIPTION

[0036] definition

[0037] The following terms will be used to describe the present invention. Unless specific definitions are set forth herein, the terms used to describe the present invention will be given their ordinary meanings as understood by those of ordinary skill in the art.

[0038] In the present disclosure, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" shall be understood to imply the inclusion of the stated integer or groups of integers, but not the exclusion of any other integer or groups of integers. It should also be noted that in the present disclosure and particularly in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising", etc. may have the meanings ascribed to them in U.S. patent law; for example, they may mean "includes", "included", "including", etc.; and terms such as "consisting essentially of", "consists essentially of" have the meanings ascribed to them in U.S. patent law, for example, they allow elements not expressly recited, but exclude elements found in the prior art or that affect the basic or novel characteristics of the present disclosure.

[0039] Furthermore, in the present disclosure and claims, unless the context requires otherwise, the word "comprise" or variations such as "includes" or "including", will be understood to imply the inclusion of stated integers or groups of integers but not the exclusion of any other integers or groups of integers.

[0040] Unless expressly stated otherwise, the use of the singular herein includes the plural (and vice versa). In addition, where the term "about" is used before a quantitative value, the present teachings also include the specific quantitative value itself, unless specifically stated otherwise. As used herein, the term "about" refers to a variation of ±10%, ±7%, ±5%, ±3%, ±1%, or ±0% from the nominal value, unless otherwise indicated or inferred.

[0041] As used herein, the terms "fine aggregate" and "coarse aggregate" are not intended to limit the size range, but are simply used to indicate that one type of aggregate contains larger particles than another type of aggregate. For example, in a cement mixture containing two types of fine sand, the fine sand with larger particles would be referred to as coarse aggregate.

[0042] The object of the present disclosure is to provide a method for producing a composite building material from a mixture of construction waste and plastic waste without adding cement. The present disclosure also provides an improved method for curing a mixture of construction waste and plastic waste, so that the plastic waste efficiently bonds and strengthens the construction waste without causing plastic oxidation (e.g., burning) and toxic gas generation during curing.

[0043] The present disclosure provides a method for preparing a composite building material, the method comprising: combining plastic waste and construction waste to form a waste mixture; and solidifying the waste mixture under anaerobic conditions to melt or soften at least a portion of the plastic waste and form a composite building material.

[0044] Construction waste used in the methods described herein may include any unwanted material generated during construction work, including but not limited to the construction and demolition of buildings, ground leveling and road paving. In certain embodiments, construction waste is substantially inert construction waste, including but not limited to concrete, asphalt, asphalt, building debris, rubble, rock, soil, aggregate, glass, brick, tile, ceramic, gypsum board and mixtures thereof.

[0045] Aggregate can be coarse aggregate, fine aggregate or a mixture thereof.

[0046] The coarse aggregate may be coarse gravel, medium gravel, fine gravel, crushed stone, pebbles, stones, concrete crushed stone, river gravel, sea gravel, crushed glass, slate waste, waste plastic, recycled coarse aggregate from waste generated after demolition, and combinations thereof.

[0047] Relative to the total weight of plastic waste and construction waste, the waste mixture may include 60% or less, 65% or less, 70% or less, 75% or less, 80% or less, 85% or less, 90% or less, or 95% or less construction waste. In certain embodiments, the waste mixture includes 60 to 95%, 60 to 90%, 60 to 85%, 60 to 80%, 60 to 75%, 60 to 70%, 60 to 65%, 65 to 95%, 70 to 95%, 75 to 95%, 80 to 95%, 85 to 95%, 90 to 95%, 70 to 90%, 70 to 85%, 70 to 80%, 70 to 75%, 75 to 90%, or 80 to 85% construction waste relative to the total weight of plastic waste and construction waste. In certain embodiments, the waste mixture includes about 60%, about 75%, about 80%, about 85%, or about 90% construction waste relative to the total weight of plastic waste and construction waste.

[0048] Prior to use in the methods described herein, the construction waste can be optionally dried to remove any residual moisture. In certain embodiments, the construction waste is air dried or dried at a temperature of 40 to 150° C., 60 to 150° C., 80 to 150° C., 80 to 130° C., 40 to 110° C., 80 to 110° C., 60 to 110° C., 90 to 110° C., or about 100° C.

[0049] Plastic waste can include any plastics discarded after use or waste produced by any industrial process or by consumers. Exemplary types of plastic waste include but are not limited to polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polystyrene, acrylonitrile butadiene styrene, polycarbonate, nylon, poly (methyl methacrylate), polyether sulfone, polyoxymethylene, polyether ether ketone, polyetherimide, polyphenylene oxide, polyphenylene sulfide, polyvinylidene fluoride, polytetrafluoroethylene and combinations thereof. In certain embodiments, plastic waste includes polyethylene, polypropylene or its mixture.

[0050] Relative to the total weight of plastic waste and construction waste, the waste mixture can contain at least 5%, at least 10%, at least 15%, at least 20%, at least 25%, at least 30%, at least 35% or at least 40% plastic waste. In certain embodiments, relative to the total weight of plastic waste and construction waste, the waste mixture contains 5 to 40%, 10 to 40%, 15 to 40%, 20 to 40%, 25 to 40%, 5 to 35%, 5 to 30%, 5 to 25%, 5 to 20%, 5 to 15%, 5 to 10%, 10 to 30%, 15 to 30%, 20 to 30%, 25 to 30%, 10 to 25% or 15 to 20% plastic waste. In certain embodiments, relative to the total weight of plastic waste and construction waste, the waste mixture contains about 10%, about 15%, about 20%, about 25% or about 40% plastic waste.

[0051] In certain embodiments, construction waste and plastic waste are mixed in any mass ratio sufficient to make the plastic waste act as an adhesive after curing. The mass ratio of construction waste and plastic waste can be 1:19 to 2:3, 1:19 to 1:4, 1:19 to 1:9, 1:9 to 2:3 or 1:4 to 2:3, respectively. Plastic waste can contain a single or multiple types of plastics.

[0052] In certain embodiments, construction waste and plastic waste can first be pulverized to reduce their particle size, which increases surface area and can improve solidification. The pulverized waste can be sieved to obtain a certain size, and then mixed with various mass ratios. There are various known methods for controlling material particle size, including cutting, tearing, crushing, chopping, grinding, pulverizing, jet grinding, hammer milling, compression grinding and tumbling grinding process and / or other mechanical techniques for reducing size. In certain embodiments, the particle size of construction waste and plastic waste is first reduced, then by sieve (including but not limited to 10mm, 5mm, 4mm, 3mm, 2mm or 1mm sieve), to improve the uniformity of waste particles.

[0053] In certain embodiments, the waste mixture is molded before solidifying the waste mixture. In order to facilitate the molding of the waste mixture, water can be added. Therefore, the method also includes combining water with plastic waste and construction waste or waste mixture, thereby forming a waste mixture with a weight water content of 5 to 80%, 5 to 70%, 5 to 60%, 5 to 50%, 5 to 40%, 5 to 30%, 5 to 20%, 10 to 20%, 15 to 20%, 5 to 15% or 5 to 10%.

[0054] The waste mixture can be optionally molded by using a mold having a desired shape to meet the requirements of the intended application of the composite building material. The molding of the waste mixture can adopt any shape that can be formed with a mold, including but not limited to spherical, cubic, cuboid, cylindrical, conical, pyramidal, hollow, sheet-like, tubular, etc.

[0055] The waste mixture may be solidified at a temperature close to or above the melting point of the plastic waste, thereby melting or softening at least a portion of the plastic waste in the waste mixture, thereby bonding the construction waste. The waste mixture may be solidified at a temperature of ±20°C, ±19°C, ±18°C, ±17°C, ±16°C, ±15°C, ±14°C, ±13°C, ±12°C, ±11°C, ±10°C, ±9°C, ±8°C, ±7°C, ±6°C, ±5°C, ±4°C, ±3°C, ±2°C, ±1°C of the melting point of the plastic waste or at the melting point of the plastic waste. In certain embodiments, the thermal treatment of the waste mixture is carried out at a temperature less than 20°C, less than 19°C, less than 18°C, less than 17°C, less than 16°C, less than 15°C, less than 14°C, less than 13°C, less than 12°C, less than 11°C, less than 10°C, less than 9°C, less than 8°C, less than 7°C, less than 6°C, less than 5°C, less than 4°C, less than 3°C, less than 2°C, or less than 1°C below the melting point of the plastic or at the melting point of the plastic. In certain embodiments, the thermal treatment of the waste mixture is carried out at a temperature less than 20°C, less than 19°C, less than 18°C, less than 17°C, less than 16°C, less than 15°C, less than 14°C, less than 13°C, less than 12°C, less than 11°C, less than 10°C, less than 9°C, less than 8°C, less than 7°C, less than 6°C, less than 5°C, less than 4°C, less than 3°C, less than 2°C, or less than 1°C above the melting point of the plastic. In certain embodiments, the thermal treatment of the waste mixture is carried out at a temperature close to the melting point of the plastic waste.

[0056] Since plastic waste contains plastic mixtures with different melting points, impurities, unknown plastics or plastics in unknown proportions, it is difficult to predict the melting point or softening point of plastic waste. Therefore, the method described in this article also includes a step of determining the melting point or softening point of the plastic mixture.

[0057] In certain embodiments, required solidification time should be enough to make at least a portion of plastic waste melting and / or softening.In certain embodiments, the waste mixture solidification time is 1 to 10 hours, 1 to 9 hours, 1 to 8 hours, 1 to 7 hours, 1 to 6 hours, 2 to 6 hours, 3 to 6 hours, 3 to 5 hours, 3 to 4 hours or 2 to 5 hours.In certain embodiments, the waste mixture solidification time is about 4 hours.

[0058] The step of solidifying the waste mixture can be carried out in air or under anaerobic conditions, wherein the anaerobic conditions are selected from vacuum or an inert atmosphere, such as nitrogen, carbon dioxide, helium, argon or a mixture thereof. Advantageously, when the step of solidifying the waste mixture is carried out in an inert atmosphere or under vacuum, oxidation of the plastic waste can be reduced or completely avoided, thereby reducing the release of toxic waste gases.

[0059] In certain embodiments, the inert atmosphere pressure / concentration supplied to the curing environment can be atmospheric pressure or any level above atmospheric pressure to reduce the oxygen content in the environment and avoid oxidation of plastic waste and generation of toxic gases. In certain embodiments, an inert gas at a gauge pressure of 10 kPa can be provided to replace oxygen in a closed space.

[0060] In certain embodiments, the vacuum in the environment for solidifying the waste mixture is any pressure below atmospheric pressure, thereby removing air in the environment and avoiding oxidation of the plastic waste. In certain embodiments, the pressure used for the environment is equal to or lower than -80 kPa gauge pressure.

[0061] In certain embodiments, the container for solidifying the waste mixture can be any container capable of controlling temperature and / or atmospheric conditions. The container can include, but is not limited to, a tank, a container, a swap body, a drum, an environmental chamber, a thermal vacuum chamber, and / or a chamber.

[0062] A silicone layer may optionally be applied to at least one surface of the composite building material to promote passive radiative cooling to reduce the surrounding temperature.

[0063] In certain embodiments, the passive radiation cooling effect of silicone coating can be improved by adding metal oxides including but not limited to magnesium oxide, aluminum oxide, titanium oxide and silicon oxide to silicone. The mass ratio of metal oxide to silicone should preferably be 5%. The passive radiation cooling effect of silicone can also be enhanced by first applying radiation cooling white paint on the solidified waste mixture, and then spraying silicone on the top of the paint. The composition of white paint includes but not limited to titanium oxide, barium sulfate and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0064] The composite building materials described herein can be used in a variety of applications, such as engineering projects, including buildings, retaining walls, partition walls, structural walls, road pavements, landscaping, and prefabricated units.

[0065] Advantageously, the composite building material may exhibit an unconfined compressive strength of at least 2.4 MPa as measured according to ASTM Standard D2166M-16. In certain embodiments, the composite building material has an unconfined compressive strength of 2.4 to 7 MPa.

[0066] The methods described herein provide many advantages, including but not limited to:

[0067] 1. Upcycling construction waste and plastic waste without using cement and raw materials, transforming construction waste and plastic waste into sustainable materials with economic value;

[0068] 2. Avoid oxidation of plastic waste and generation of toxic gases during solidification of waste mixture, thus forming better bonds between wastes and producing stronger materials;

[0069] 3. Improve production flexibility and efficiency by simplifying waste sorting and reducing curing temperature control requirements;

[0070] 4. Improving the functionality of the developed material by providing passive radiative cooling by coating the material surface with silicone. The cooling effect can be enhanced by adding metal oxides to the silicone and by applying a radiative cooling white paint before applying the silicone.

[0071] 5. Reduce dependence on conventional building materials and minimize CO2 from the construction industry 2 emissions to promote carbon neutrality.

[0072] Example

[0073] Example 1 - Strength of construction waste with and without plastic waste (i.e., PE) after curing in air

[0074] In this embodiment, construction waste including building debris, crushed stone, stone, concrete rubble and soil was used. Plastic waste corresponding to PE was also considered. In order to remove moisture, the two wastes were oven dried at 100°C for one day. Then, they were crushed into small pieces using a grinder and sieved to improve the homogeneity of the test specimens. The particle sizes of construction waste and plastic waste were less than 2mm and 48μm, respectively. Plastic waste was added to construction waste in different mass ratios (including 5%, 10% and 20%). The waste was then thoroughly mixed with deionized water. The weight water content of the waste mixture was about 14%. For the control group, construction waste was mixed only with deionized water. The mixture was compacted in a metal mold to form a cylindrical specimen with a diameter of 50mm and a height of 100mm. The dry density of the specimen was 1,410kg / m 3 . Control samples without plastic waste were cured at four temperatures in air and at two temperatures in vacuum. The four temperatures included 150°C, 200°C, 250°C and 265°C, while vacuum conditions used 325°C and 340°C. In addition, the samples containing plastic waste were cured in air at 150°C, which is slightly above the melting point of polyethylene (i.e., about 110 to 145°C). The curing time for all test conditions was 4 hours. Each test condition had three replicates. After curing, unconfined compression tests were performed in accordance with ASTM standard D2166M-16. The specimens were tested at 1 mm min -1 During shearing, the axial stress and axial deformation of the specimen are measured using a load cell and a linear variable differential transformer, respectively. The measured axial stress peak value indicates the strength of the specimen.

[0075] Figure 1 It represents the unconfined compressive strength of untreated construction waste after curing at different temperatures. The compressive tests were repeated three times for each temperature considered. When the curing temperature increased from 150°C to 340°C, the strength of the construction waste varied from 59 kPa to 115 kPa, with an average value of about 92 kPa. The maximum strengths of the specimens after curing in air and vacuum were 108 kPa and 115 kPa, respectively. The difference in the maximum strength of the specimens cured using the two methods was less than 10%. These results show that the strength of pure construction waste is independent of the curing temperature and gas, as no binder is added. Figure 2The strength of construction waste containing plastic waste after curing in air is shown in Figure 2 when different amounts of plastic waste (i.e., PE) are added to construction waste. The strength of construction waste increases with the amount of plastic waste added because more plastic waste is available to bind construction waste after curing. When the amount of added plastic waste reaches 20%, the strength of construction waste containing plastic waste increases to 4.7 MPa, which is higher than the strength generally required for conventional gypsum partitions (GA, 2019). The increase in strength after treatment is also about 54 times that of untreated construction waste. Therefore, it is feasible to use construction waste containing some specific types of plastic waste to produce materials with different applications by curing in air.

[0076] Example 2 - Construction waste containing plastic waste (i.e., PP) after solidification in different types of gases Spend

[0077] This example considers the solidification of construction waste containing another plastic waste in air and in an environment with an inert gas or vacuum applied. Construction waste includes building debris, crushed stone, stone, concrete rubble and earth material, while the type of plastic waste is PP. Initially, both construction waste and plastic waste are oven dried at 100°C for 24 hours to remove any moisture. In order to ensure the homogeneity of the test specimens, the waste is crushed into small pieces using a grinder and passed through sieves of different sizes. The particle size of the construction waste is less than 2mm. For plastic waste, a size of less than 48μm is selected to prepare the specimens solidified in air, while a size of less than 500μm is selected to prepare the specimens solidified in inert gas and vacuum. To prepare the test specimens, the sieved plastic waste is first added to the sieved construction waste in different mass ratios. Then, deionized water is uniformly added to the waste mixture. Afterwards, the mixture is compacted in a metal mold to form a cylindrical specimen with a diameter of 50mm and a height of 100mm. Three test series were carried out in this example. In the first series, two amounts (i.e., 5% and 10%) of plastic waste were added. The dry density and gravimetric moisture content of the samples were 1410 kg / m 3and 14%. Three curing temperatures were used, namely 100°C, 150°C and 185°C. Only the latter was above the melting point of plastic waste (i.e., about 160 to 170°C). And the specimens were cured in air. For the second series, 5% of plastic waste was added to the construction waste. The dry density and moisture content were the same as in the first series, but the highest temperature used in the first series was chosen to cure the specimens. And various types of gases (i.e., air, nitrogen and vacuum) were used for curing. The gauge pressures of nitrogen and vacuum were 10kPa and -80kPa, respectively. The last test series considered curing the specimens in a vacuum at a gauge pressure of -80kPa and focused on 10% and 40% of plastic waste. The initial density and weight moisture content of the specimens were 1240kg / m 3 and 14%. The curing temperature was also the same as the maximum temperature used in the first test series. In all test series, the duration of curing was 4 hours. Thereafter, unconfined compression tests were performed based on ASTM standard D2166M-16 to measure the strength of the waste mixture after curing under different conditions. The specimens were tested at 1 mm min -1 The axial stress and deformation of the specimen were measured using a load cell and a linear variable differential transformer, respectively. The measured peak stress represents the unconfined compressive strength of the specimen.

[0078] Figure 3 The strength of construction waste containing plastic waste (PP) after curing in air is shown. When the curing temperature (i.e., 100°C and 150°C) is lower than the melting point of the plastic waste, the strength of the waste mixture increases with the amount of plastic waste added, because more plastic waste particles may obtain enough energy to melt and bond the construction waste. Compared with the strength of untreated construction waste, the strength of construction waste containing 5% and 10% plastic waste increased by at least 65% and 95%, respectively. However, the strength of the waste decreases with the increase of curing temperature. At the highest curing temperature, the sample prepared with 5% plastic waste collapsed after curing, while the strength of construction waste containing 10% plastic waste was even lower than that of untreated construction waste. These results show that curing in air at a temperature higher than the melting point of plastic waste does not always ensure that plastic waste can melt to reinforce construction waste. The presence of construction waste itself and impurities in the waste will affect the melting point of plastic waste. It is difficult and impractical to accurately control the curing temperature to achieve melting. Furthermore, when solidified in air, plastic waste may oxidize (eg, burn) and generate toxic gases. Therefore, solidifying the waste mixture in an environment containing an inert gas or in a vacuum overcomes the limitations of solidifying the waste mixture in air. Figure 4The compressive strength of construction waste with 5% plastic waste added after curing in different types of gases is presented. The curing temperatures considered are Figure 3 The maximum temperature shown in Figure 1 is the same as that in Figure 2. When the samples were cured in air, they collapsed after curing. Only the samples cured in nitrogen and vacuum showed a material strength that was at least 8 times higher than that of construction waste without plastic waste. This further confirms that the new method can avoid oxidation of plastic waste and is beneficial for the reinforcement of construction waste with plastic waste. In order to have a more comprehensive understanding of the properties of the waste mixture prepared by the new method, different contents of plastic waste were considered and the Figure 3 Curing is carried out at the highest temperature considered. Figure 5 The unconfined compressive strength of construction waste mixed with different amounts of PP waste after curing in vacuum is shown. The strength of the waste mixture increases with the amount of plastic waste added. The strength of construction waste containing 10% and 40% plastic waste increased by about 17 times and 75 times, respectively, relative to untreated construction waste. All of the above results show that the newly pioneered method overcomes the limitations of the existing technology in reusing plastic waste to bond construction waste. This type of new method is also more comprehensive and applicable to a variety of plastic waste. More importantly, the strength of construction waste containing 40% plastic waste exceeds the strength required for typical gypsum partitions (i.e., 2.4MPa) (GA, 2019) and meets the strength requirements of general-purpose bricks (i.e., 7MPa) (BS 6073-1, 1981). This shows that the sustainable cement-free material prepared by the new method is suitable for a variety of applications including the construction of partitions and pavements. The pioneered new method can also reduce dependence on typical carbon-intensive building materials such as cement and concrete to promote sustainable development and achieve carbon neutrality.

[0079] It is to be understood that within the principle and scope of the present invention as expressed by the accompanying key features, those skilled in the art may make numerous additional changes to the details, materials, and steps described and illustrated to explain the nature of the subject matter.

[0080] References

[0081] Akinyele,JO,Igba,UT,Adigun,BG,2020.Effect of waste PET on thestructural properties of burnt bricks.Scientific African,7,e00301.

[0082] BS 6073-1,1981.British Standard-Precast concrete masonry units(Part1:Specification for precast concrete masonry units).British StandardsInstitution,United Kingdom.

[0083] Dalhat,M.A.,Wahhab,H.A.A.,2016.Cement-less and asphalt-less concretebounded by recycled plastic.Construction and Building Materials,119,206-214.

[0084] Eurostat,2022.Generation of waste by waste category,hazardousness andNACE Rev.2activity.(assessed on 16June 2023)

[0085] GA,2019.GA-235-Gypsum board typical mechanical and physicalproperties.Gypsum Association,United State.https: / / www.americangypsum.com / sites / default / files / 2022-01 / ga-235_gypsum_board_typica l_mechanical_and_physical_properties.pdf(Assessed on 22June 2023)

[0086] Ibrahim,H.A.,Goh,Y.,Ng,Z.A.,Yap,S.P.,Mo,K.H.,Yuen,C.W.,Abutaha,F.,2020.Hydraulic and strength characteristics of pervious concrete containing ahigh volume of construction and demolition waste as aggregates.Constructionand Building Materials,253,119251.

[0087] IPCC(Intergovernmental Panel on Climate Change),2019.Global Warmingof 1.5℃.https: / / www.ipcc.ch / site / assets / uploads / sites / 2 / 2022 / 06 / SR15_Full_Report_HR.pdf[assessed on 16 June 2023]

[0088] Monteiro,P.J.,Miller,S.A.,Horvath,A.,2017.Towards sustainableconcrete.NatureMaterials,16(7),698-699.

[0089] Nizamuddin,S.,Jamal,M.,Gravina,R.,Giustozzi,F.,2020.Recycled plasticas bitumenmodifier:The role of recycled linear low-density polyethylene inthe modification ofphysical,chemical and rheological properties ofbitumen.Journal of Cleaner Production,266,121988.

[0090] QIRI(Qianzhan Industrial Research Institute),2018.Report of marketresearch andinvestment forecast analysis on China construction and demolitionwaste disposal industry,2022-2027.https: / / bg.qianzhan.com / report / detail / 459 / 181228-0c3486f5.html(assessed on16 June 2023)

[0091] Shi,C.,Li,Y.,Zhang,J.,Li,W.,Chong,L.,Xie,Z.,2016.Performanceenhancement ofrecycled concrete aggregate–a review.Journal of CleanerProduction,112,466-472.Statista,2023.Global plastic production 1950-2021.https: / / www.statista.com / statistics / 282732 / global-production-of-plastics-since-1950 /

[0092] (assessed on 16 June 2023)

[0093] Sun,P.,Huang,X.,Xu,C.,2022.Flashpoint and burning of thin moltenplastic pool abovehot boundary.Applied Thermal Engineering,215,118931.

[0094] UKGBC(UK Green Building Council),2015.Tackling embodied carbon inbuildings.https: / / www.c40knowledgehub.org / s / article / Tackling-embodied-carbon-in-buildings?language=en_US(assessed on 16 June 2023)

[0095] USEPA(United States Environmental Protection Agency),2020.Advancingsustainablematerials management:2018 Facts and figures report.https: / / www.epa.gov / facts-and-figures-about-materials-waste-and-recycling / advancing-sustainable-materials-management(assessed on 16 June 2023)

[0096] Vollmer,I.,Jenks,M.J.,Roelands,M.C.,White,R.J.,van Harmelen,T.,deWild,P.,vander Lann,G.P.,Meirer,F.,Keurentjes,J.T.F.,Weckhuysen,B.M.,2020.Beyond mechanicalrecycling:Giving new life to plastic waste.AngewandteChemie,59(36),15402-15423.Zulkernain,N.H.,Gani,P.,Chuan,N.C.,Uvarajan,T.,2021.Utilisation of plastic waste asaggregate in construction materials:Areview.Construction and Building Materials,296,123669。

Claims

1. A method for preparing a composite building material, the method comprising: combining plastic waste and construction waste to form a waste mixture; as well as The waste mixture is solidified under oxygen-free conditions, thereby melting or softening at least a portion of the plastic waste and forming the composite building material.

2. The method of claim 1, wherein the construction waste comprises concrete, asphalt, asphalt, rubble, rock, aggregate, building debris, crushed stone, stone, concrete rubble, earth, broken glass, bricks, tiles, ceramics, gypsum board or a mixture thereof.

3. The method according to claim 1, wherein the plastic waste comprises polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polystyrene, acrylonitrile butadiene styrene, polycarbonate, nylon, polymethyl methacrylate, polylactic acid (polylactide), polyether sulfone, polyoxymethylene, polyether ether ketone, polyetherimide, polyphenylene ether, polyphenylene sulfide, polyvinylidene fluoride, polytetrafluoroethylene or a mixture thereof.

4. The method of claim 1, wherein the plastic waste comprises polyethylene, polypropylene or a mixture thereof.

5. The method of claim 1, wherein the composite building material comprises at least 5% of the plastic waste relative to the total weight of plastic waste and construction waste.

6. The method of claim 1, wherein the composite building material comprises at least 10% of the plastic waste relative to the total weight of plastic waste and construction waste.

7. The method of claim 1, wherein the step of combining plastic waste and construction waste further comprises combining water to form the waste mixture having a water content of 5 to 20% by weight; and molding the waste mixture prior to curing the waste mixture.

8. The method according to claim 1, wherein solidifying the waste mixture is carried out at a temperature of ±20°C of the melting point of the plastic waste.

9. The method according to claim 1, wherein solidifying the waste mixture is carried out at a temperature of ±5°C of the melting point of the plastic waste.

10. The method of claim 1, further comprising the step of determining a melting point of the plastic waste.

11. The method of claim 1, wherein the oxygen-free condition comprises a vacuum or an inert atmosphere comprising nitrogen, carbon dioxide, helium, argon, or a mixture thereof.

12. The method of claim 1, wherein the composite building material has an unconfined compressive strength of at least 2.4 MPa as measured according to ASTM D2166M-16.

13. The method according to claim 1, wherein the construction waste comprises building debris, crushed stone, stone, concrete rubble, earth or a mixture thereof; the plastic waste comprises polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polystyrene or a mixture thereof; the composite building material comprises at least 5 to 40% of the plastic waste relative to the total weight of the plastic waste and construction waste; the solidification of the waste mixture is carried out at a temperature of ±20°C of the melting point of the plastic waste; and wherein the oxygen-free condition comprises a vacuum or an inert atmosphere, and the inert atmosphere comprises nitrogen, carbon dioxide, helium, argon or a mixture thereof.

14. The method of claim 13, wherein the composite building material has an unconfined compressive strength of at least 2.4 MPa as measured according to ASTM D2166M-16.

15. The method according to claim 1, wherein the construction waste comprises building debris, crushed stone, stone, concrete rubble, earth or a mixture thereof; the plastic waste comprises polyethylene, polypropylene or a mixture thereof; the composite building material comprises at least 10 to 40% of the plastic waste relative to the total weight of the plastic waste and the construction waste; the solidification of the waste mixture is carried out at a temperature of ±5°C of the melting point of the plastic waste; and wherein the oxygen-free condition comprises a vacuum or an inert atmosphere, and the inert atmosphere comprises nitrogen, carbon dioxide, helium, argon or a mixture thereof.

16. The method of claim 14, wherein the composite building material has an unconfined compressive strength of 2.4 MPa to 7 MPa as measured according to ASTM D2166M-16.

17. The method of claim 15, further comprising the step of determining a melting point of the plastic waste.

18. The method of claim 1, further comprising applying a surface treatment to at least one surface of the composite building material, wherein the surface treatment comprises a radiative cooling coating, a radiative cooling paint, or a mixture thereof.

19. The method of claim 18, wherein the radiative cooling coating comprises silicone and a metal oxide selected from the group consisting of magnesium oxide, aluminum oxide, titanium oxide, and silicon oxide.

20. The method of claim 18, wherein the radiative cooling coating comprises titanium dioxide, barium sulfate, and polyvinylidene fluoride-hexafluoropropylene copolymer.